Evaluation of p53, Caspase-3, Bcl-2, and Ki-67 markers in oral squamous cell carcinoma and premalignant epithelium in a sample from Alava Province (Spain) - Bascones-Martínez, Antonio (Medicina Oral S.L., 2013)
Objectives: The objective of this study was to determine whether alterations in the expression of p53, caspase-3 Bcl-2, and ki-67 appear early in premalignant oral epithelium and show clonal behavior. Study Design: Samples from 41 tumors with their adjacent non-tumor epithelia were immunohistochemically analyzed using monoclonal antibodies that recognize p53, caspase-3, Bcl-2, and Ki-67 Results: A statistically significant association was found between the expression in tumor and adjacent epithelium of p53, caspase-3, and Bcl-2 but not of k-67. A significant association was observed between the expression of ki-67 and p53 in both localizations. In non-tumor (premalignant) epithelium samples, there was a significant inverse relationship between the expressions of p53 and caspase-3 and a significant direct relationship between the expressions of p53 and Bcl-2. Conclusions: Alterations in these proteins appear to operate in combination with premalignant epithelia to create hyperproliferative cell states that favor the acquisition of summative oncogenic errors that confer invasive capacity. Key words:Cell cycle, apoptosis, p53, caspase-3, Bcl-2, Ki-67.